Internalization of Religious Values through the Ta’lim Jami’atul Muwahhidin Council of Sampang Madura - Ivan Luthfi Amirudin (International Journal of Religion and Social Community, 2024)
This article aims to reveal the success of Ta’lim Jami’atul Muwahhidin in internalizing religious values for the people of Sampang, Madura. This study uses a qualitative approach to produce a valid description of the research object in sentences. The researcher uses a type of case study research. The data of this study came from the caregivers, administrators and worshippers of the Ta’lim Jam’iatul Muwahhidin Sampang Council, in the collection of data, the researcher used three rarities, including observation, interview, and documentation. The researcher used the Miles and Huberman model to analyse the data. The results of the research show that the purpose of internalization in the ta’lim jami’atul Muwahhidin assembly is to make the congregation know Allah SWT, know the Prophet Muhammad Saw, make the congregation have a good personality, and protect the congregation from the misguided. The values internalised in the congregation are monotheism, tolerance, humility, tawakal, patience, loman, ngalah, akas and professionalism. The internalization process uses three methods, namely, the discussion method, the lecture method, the advice method, and the exemplary method. The impact of internalizing religious values, namely, pilgrims repent of nasukha and zuhud for the luxury of the world and better morals.